Prevalence of Hookah Smoking among University Students in Iran: A Meta-Analysis of Observational Studies - Mahmoud KHODADOST; Khadije MAAJANI; Abbas ABBASI-GHAHRAMANLOO; Morteza NASERBAKHT; Ebrahim GHODUSI; Fatemeh SARVI; Azar MOHAMMADZADEH; Seyed Abbas MOTEVALIAN; Ahmad HAJEBI (Tehran University of Medical Sciences, 2020)
Background: The rise in popularity of waterpipe smoking among younger people cause increase its deleterious effects on health in recent years. The aim of this study was to estimate the pooled prevalence of water-pipe smoking in university students in Iran. Methods: We performed the literature search from 1946 to January 21, 2019, in several international and national databases such as Medline/PubMed, Web of Science, Scopus, Google Scholar, Magiran, Iranmedex, and IranPsych. To investigate the between-study heterogeneity we used the chi-squared test and I2 index. We used a random-effects model to estimate the pooled prevalence of water-pipe smoking. The potential source of heterogeneity was assessed by subgroup analysis and meta-regression. Results: According to the eligibility criteria, we included 37 relevant studies in our meta-analysis. The pooled prevalence of lifetime water-pipe smoking was 25% (95% CI: 22-29) and in male and female subgroups was 37% (95%CI: 30-45), 17% (95%CI: 15-19) respectively. The pooled prevalence of water-pipe smoking in last year was 21% (95%CI: 16-25) and in last month was 8% (95%CI: 5-11). Results of meta-regression analysis showed that there was not any significant association between suspected variables and the prevalence of water-pipe smoking. Conclusion: The higher prevalence rate of water pipe smoking among university students indicates the emergency need for planning preventive program.